APPLICATION OF AMARANTH FLOUR IN BAKERY PRODUCTS WITHIN FOOD TECHNOLOGY - M. X. Khamrakulova; N. Y. Bobojonova (Modern American Journals, 2025)
The present study explores the application of amaranth (Amaranthus spp.) flour in food technology, with a particular emphasis on its integration into bakery products. Amaranth, recognized as a pseudocereal, possesses a unique nutritional profile characterized by high-quality proteins, essential amino acids (such as lysine), dietary fiber, and a rich array of micronutrients including calcium, iron, and magnesium. The incorporation of amaranth flour into bread and related bakery formulations significantly enhances their functional and biological value. Experimental results indicate improvements in the nutritional content, antioxidant capacity, and digestibility of the final products. Moreover, the use of amaranth flour positively influences technological properties such as dough stability, moisture retention, and shelf-life extension. These findings support the potential of amaranth flour as a functional ingredient that aligns with current trends toward health-promoting, gluten-free, and sustainable food products. The study contributes to the advancement of innovative food processing practices and offers valuable insights for the development of nutritionally enriched bakery items.
Keywords: Amaranth flour, bakery products, functional food, nutritional enhancement, food technology, pseudocereals, dietary fiber, antioxidant activity